Antibiotic Prescription Fills for Acute Conjunctivitis among Enrollees in a Large United States Managed Care Network - Shekhawat, Nakul S; Shtein, Roni M; Blachley, Taylor S; Stein, Joshua D (Ophthalmology (Rochester, Minn.), 2017)
Antibiotics are seldom necessary to treat acute conjunctivitis. We assessed how frequently patients with newly diagnosed acute conjunctivitis fill prescriptions for topical antibiotics and factors associated with antibiotic prescription fills. Retrospective, observational cohort study. A total of 340 372 enrollees in a large nationwide United States managed care network with newly diagnosed acute conjunctivitis, from 2001 through 2014. We identified all enrollees newly diagnosed with acute conjunctivitis, calculating the proportion filling 1 or more topical antibiotic prescription within 14 days of initial diagnosis. Multivariate logistic regression assessed sociodemographic, medical, and other factors associated with antibiotic prescription fills for acute conjunctivitis. Geographic variation in prescription fills also was studied. Odds ratios (ORs) with 95% confidence intervals (CIs) for filling an antibiotic prescription for acute conjunctivitis. Among 340 372 enrollees with acute conjunctivitis, 198 462 (58%) filled ≥1 topical antibiotic prescriptions; 38 774 filled prescriptions for antibiotic-corticosteroid combination products. Compared with whites, blacks (OR, 0.89; 95% CI, 0.86-0.92) and Latinos (OR, 0.83; 95% CI, 0.81-0.86) had lower odds of filling antibiotic prescriptions. More affluent and educated enrollees had higher odds of filling antibiotic prescriptions compared with those with lesser affluence and education (P < 0.01 for all). Compared with persons initially diagnosed with acute conjunctivitis by ophthalmologists, enrollees had considerably higher odds of antibiotic prescription fills if first diagnosed by an optometrist (OR, 1.26; 95% CI, 1.21-1.31), urgent care physician (OR, 3.29; 95% CI, 3.17-3.41), internist (OR, 2.79; 95% CI, 2.69-2.90), pediatrician (OR, 2.27; 95% CI, 2.13-2.43), or family practitioner (OR, 2.46; 95% CI, 2.37-2.55). Antibiotic prescription fills did not differ for persons with versus without risk factors for development of serious infections, such as contact lens wearers (P = 0.21) or patients with human immunodeficiency virus infection or AIDS (P = 0.60). Nearly 60% of enrollees in this managed care network filled antibiotic prescriptions for acute conjunctivitis, and 1 of every 5 antibiotic users filled prescriptions for antibiotic-corticosteroids, which are contraindicated for acute conjunctivitis. These potentially harmful practices may prolong infection duration, may promote antibiotic resistance, and increase costs. Filling antibiotic prescriptions seems to be driven more by sociodemographic factors and type of provider diagnosing the enrollee than by medical indication.